Othering Albanian Muslim Masculinities: A Case Study of Albanian Football Players - Ferizaj, Adem (Occhialì, 2019)
This paper will look at how Albanian Muslim masculinities are ‘othered’ in German-speaking and Albanian-speaking discourses. Whereas Western political circles tend to be reluctant regarding the Euro-Atlantic integration of Albania and Kosovo due to their Islamic cultural heritage, Albanian political elites have adopted a discursive strategy of erasure with regards to their Muslimness in pursuit of their Euro-Atlantic ambitions. Albanian football is an interesting case study, as a considerable part of Albanian footballers are famous in Europe and highlight Islam as an integral part of their Albanian identity. This paper suggests the following: Albanian Muslim men are tacitly ‘othered’ due to the inherent Orientalist episteme of Albanians in Euro-Atlantic discourses, and the othering of these masculinities becomes explicit when their behaviour is interpreted as ‘foreign’ to Western values and lifestyles – one such example would be to highlight Islam as part of their identity, as several Albanian footballers do. At worst, masculinities of Albanian Muslim footballers are described as ‘uncultivated’, unwilling to integrate into Western society, ideologically dangerous, and ‘non-European’. This characterization translates into subordinate masculinities toward European secular hegemonic masculinities